Assessment of Customers Satisfaction in Mass Rapid Transit (MRT) Using Importance-Performance Analysis (IPA) - Samsudin N.S.S.; Ismail N.; Norhisham S.; Zaini N.; Bakar M.F.A.; Azlan N.N.I.M.; Ron Buking R.A.C. (Springer Science and Business Media Deutschland GmbH, 2023)
Developing countries; Mass transportation; Quality control; Quality of service; Rapid transit; Reliability analysis; Sales; Customers' satisfaction; Importance-performance analyse; Importance-performance analysis; Malaysia; Mass rapid transit; Performance; Public transportation; Quality-of-service; Rail transportation; Transit use; Customer satisfaction